Estimating a Non-Linear Economic Model for a Small-Scale Pyrolysis Unit - Alok Dhaundiyal; András Máté Betovics; Laszlo Toth (Energies)
This article used control theory to derive a non-linear exergoeconomic model for a bench-scale pyrolysis unit. A combination of an autoregressive model with an exogenous input model was involved to investigate the energy system. The economic prospects of the unit were also examined by assigning the cost to the exergy content of the energy stream. The analysis covered the detailed evaluation of the design and performance of an updraft system. Thermally processed pine waste was used as a feedstock for the reactor. The developed model fits well with the validation data extracted through the experimental findings. The exergy cost flow rate of processed pine waste was estimated to be 0.027 ¢/s−1. The exergoeconomic factor was the highest for pyrolysis oil and charcoal generated as the end products of the thermal decomposition of processed pine waste.